Reassessing European Union Limits: What Role for the new Regional Partnerships? - Adriana Berbec (Romanian Journal of European Affairs)
As every enlargement brings new neighbours to the European Union, the European Neighbourhood Policy is facing new challenges regarding its policy towards the countries in its proximity. Although the ENP does not offer perspectives for accession, nor does it preclude it, new forms of cooperation between the EU and its neighbours are taken into consideration as an alternative to full membership. This essay will analyze how the latest enlargements have brought new opportunities and challenges to the EU in relation to its new neighbours, the role of the „Eastern Partnership” and the „Union for Mediterranean” initiatives in fostering cooperation with the contiguous countries and whether these community projects, together with the ENP, can have a contribution to the understanding of what the EU limits are.